Recent developments in horizontal gene transfer with the adaptive innovation of fermented foods. Issue 5 (17th February 2023) - Wang, Ruhong; Wu, Junrui; Jiang, Nan; Lin, Hao; An, Feiyu; Wu, Chen; Yue, Xiqing; Shi, Haisu; Wu, Rina
Abstract: Horizontal gene transfer (HGT) has contributed significantly to the adaptability of bacteria, yeast and mold in fermented foods, whose evidence has been found in several fermented foods. Although not every HGT has biological significance, it plays an important role in improving the quality of fermented foods. In this review, how HGT facilitated microbial domestication and adaptive evolution in fermented foods was discussed. HGT can assist in the industrial innovation of fermented foods, and this adaptive evolution strategy can improve the quality of fermented foods. Additionally, the mechanism underlying HGT in fermented foods were analyzed. Furthermore, the critical bottlenecks involved in optimizing HGT during the production of fermented foods and strategies for optimizing HGT were proposed. Finally, the prospect of HGT for promoting the industrial innovation of fermented foods was highlighted. The comprehensive report on HGT in fermented foods provides a new trend for domesticating preferable starters for food fermentation, thus optimizing the quality and improving the industrial production of fermented foods.